2012
DOI: 10.3899/jrheum.110566
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Femoropopliteal Arteries in Giant Cell Arteritis: Clinical and Color Duplex Sonography

Abstract: Femoropopliteal artery involvement appears to be a clinically relevant manifestation of GCA, frequently leading to symptomatic lower extremity ischemia. CDS of the femoropopliteal arteries is a noninvasive diagnostic tool for detection of lower extremity vasculitis in GCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 26 publications
1
35
0
4
Order By: Relevance
“…GCA of femoropopliteal arteries was present in half of the patients, developed bilaterally and every second patient with positive sonography fi nding was symptomatic either in means of claudication or symptoms of critical limb ischemia. In contrast to atherosclerotic etiology, ischemic symptoms in patients with GCA progressed rapidly and lead to development of limb-threatening ischemia within very short of time (15). Assie and his colleagues came up with similar results demonstrating a common presence of upper and lower extremity involvement in GCA even in early phase of disease (16).…”
Section: Giant-cell Arteritismentioning
confidence: 92%
See 1 more Smart Citation
“…GCA of femoropopliteal arteries was present in half of the patients, developed bilaterally and every second patient with positive sonography fi nding was symptomatic either in means of claudication or symptoms of critical limb ischemia. In contrast to atherosclerotic etiology, ischemic symptoms in patients with GCA progressed rapidly and lead to development of limb-threatening ischemia within very short of time (15). Assie and his colleagues came up with similar results demonstrating a common presence of upper and lower extremity involvement in GCA even in early phase of disease (16).…”
Section: Giant-cell Arteritismentioning
confidence: 92%
“…Claudication can be managed by conservative treatment in most cases, but severe deterioration leading to even limb amputation is also a threat (16,17,18). Some studies using ultrasound also found quite a frequent presence of atherosclerotic plaques in lower extremity arteries in patients older than 50 years (15,19). Atherosclerosis must be recognised as a possible co-factor in elderly but if acute bilateral and rapidly progressive claudication occurs especially in association with a systemic infl ammatory disorder of unknown origin suspicion for possible extracranial GCA must be taken into consideration (15,1 7).…”
Section: Giant-cell Arteritismentioning
confidence: 99%
“…Of note, vasculitis of the subclavian and/or axillary arteries was detected in 74.2% of our patients with involvement of the femoropopliteal arteries and in all except 1 patient with carotid artery involvement by CDS criteria 2,4 . Therefore, a sonographic finding consistent with vasculitis of the proximal arm arteries strongly supports a suspected diagnosis of GCA of the lower extremity or carotid arteries.…”
Section: To the Editormentioning
confidence: 98%
“…We appreciate the comments from Milchert, et al 1 on our study evaluating the involvement of femoropopliteal arteries in giant cell arteritis (GCA) 2 . In their letter, they describe 2 cases with different clinical manifestations of extracranial GCA, including 1 patient with suspected vasculitis of the lower extremities.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation